If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(2y) * 6 + 7(6) = 15(3) Remove parenthesis around (2y) -1 * 2y * 6 + 7(6) = 15(3) Reorder the terms for easier multiplication: -1 * 2 * 6y + 7(6) = 15(3) Multiply -1 * 2 -2 * 6y + 7(6) = 15(3) Multiply -2 * 6 -12y + 7(6) = 15(3) Multiply 7 * 6 -12y + 42 = 15(3) Reorder the terms: 42 + -12y = 15(3) Multiply 15 * 3 42 + -12y = 45 Solving 42 + -12y = 45 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + -12y = 45 + -42 Combine like terms: 42 + -42 = 0 0 + -12y = 45 + -42 -12y = 45 + -42 Combine like terms: 45 + -42 = 3 -12y = 3 Divide each side by '-12'. y = -0.25 Simplifying y = -0.25
| y=1/4x+2 | | y+1/4x+2 | | 15+3(x-1)=24 | | 19+13z=9+12z | | 4b^2-5b+1=0 | | 2/5x+3=4(7/8+1x/12) | | (y+9)(y+1)=0 | | 13-7x=52-14x | | (8+u)(2u+9)=0 | | 287/6/11 | | X^2+12x+120=0 | | -2(w-1)(-w-4)=0 | | X^2+12x+120=o | | 13+10x=53-24x | | 282/6/11 | | x^2+60=0 | | (4y-3)+y=y+(5-y) | | (7-2)/5 | | f(x)=5x^2-7 | | (3+3)(3+3)= | | 3(p-10)/4p | | -1/5x^2=0 | | 5/16+6=5/4 | | 61+4x=9x+22 | | -5=4+a+(-3) | | 22=10+w+4 | | Y=x^2-4x+5 | | -7+p+9=-2 | | 3x-5x=18 | | d+6+(-8)=4 | | 8/y-6/y2 | | y=9x-8y-8x |